The Implications of Delta-9-tetrahydrocannabinol on Localized Immune and Hormonal Responses Mediated by Trophoblasts of the Human Placenta - Gurm, Harmeet (My University, 2021)
Over the approximate nine months of its intrauterine existence, the development of the fetus is supported by the human placenta. This transient organ is central to pregnancy success as it facilitates maternal-fetal exchange, immunological tolerance, and hormone production. Villous trophoblasts mediate placental formation by engaging in a continuous turnover process of proliferation, differentiation, fusion, and apoptosis. In doing so, cytotrophoblasts and syncytiotrophoblasts maintain the integrity of the outer placental lining known as the syncytium. Exposure to drugs, however, can compromise placental establishment, which can in turn adversely impact pregnancy and fetal health. Specifically, cannabis is widely used by women of reproductive age and during pregnancy. While maternal cannabis use is linked to poor outcomes such as preterm birth and neurodevelopmental delays in exposed children, the underlying mechanisms are not well-defined. First, we characterized a functionally relevant cell line to model differentiation and fusion. In a comparison of the BeWo and BeWo b30 cell lines, our findings demonstrated that both models similarly undergo fusion. We then explored the implications of exposure to delta-9- tetrahydrocannabinol (∆9-THC) on the immunological roles of villous trophoblasts. We observed that cytotrophoblast differentiation and fusion were associated with localized inflammation due to elevated interleukin-2 (IL-2) and tumour necrosis factor-alpha (TNF-α) but inhibited interleukin-4 (IL-4) and interleukin-10 (IL-10) production. ∆9-THC exposure impaired this T helper 1/2 cytokine balance through decreased IL-2 and TNF-α as well as increased IL-4 and IL-10 levels. Subsequently, we investigated the effects of ∆9-THC in TNF-α- and IL-10-dominant environments, to represent inflammatory and immunomodulatory microenvironments, respectively. Coincident with inflammation, ∆9-THC attenuated trophoblast fusion and the biosynthesis of steroid hormones, progesterone and cortisol, through perturbed cytochrome P450 regulation. This thesis ultimately lays a foundation for understanding how cannabis use during pregnancy may compromise the fusogenic, immune and endocrine functions of villous trophoblasts in the placenta.
Keywords: Placenta; Pregnancy; Trophoblast; Th1/Th2 cytokines; Delta-9-tetrahydrocannabinol